Packing Facilities Fruits & Vegetables - Gast, Karen L. B. (My University, 1998)
This publication explains packing facilities for fruits and vegetables.
MF2322_1998_01
Keywords: MF2322; Fruits and Vegetables; Equipment and structures; MF